(untitled) (The Pretoria Student Law Review, 2021)
South Africa has become a magnet to a larger group of foreign migrants than the global average. This is due to the fact that it is a front-runner, economically speaking, in Sub-Sahara Africa with a reputation of political stability. The South African Constitution is the supreme law of the Republic, to which all other law is subject. South Africa’s constitutional framework, coupled with immigration legislation and policies, aim to promote the rights enshrined in the Bill of Rights for all individuals living within the borders of the Republic. While certain rights are expressly reserved for citizens only and are largely of a civil or political nature, the remaining rights are those that ‘everyone’, including foreign nationals, may enjoy. Non-citizens within the borders of the Republic receive, inter alia, the protection of South Africa’s basic constitutional values; in particular the right to equality, human dignity and freedom. Socio-economic rights, subject to the limitations clause in section 36 of the Constitution, are also made available to everyone. This includes both citizens and foreign nationals. These rights can be found in section 25, 26, 27, 28 and 29 of the Constitution and relate to issues of access to land, housing, health care, food, social security and education. The focus of this paper will be the right of access to social security for non-citizens, particularly migrants, in South Africa. Who falls within the scope of the term ‘everyone’ as found in section 27 of the Constitution? The international perspective on the issue of social exclusion of non-citizens from accessing social security benefits is briefly dealt with, followed by a discussion of the South African perspective on the matter. The approach of the South African Constitutional Court in respect of the protection of the rights of noncitizens will then be discussed. The European approach to the matter, including the approach of European courts, will then be examined. The concluding paragraphs entail an evaluation of the improvements that can be made to the South African social security system as inspired by the European approach.